“The body overseas, but the heart remains in China”? – China’s diaspora politics and its implications - Schäfer, Carsten (Border Crossing, 2019)
Migration studies mostly focus on processes of immigration. While integration, acculturation or incorporation are important fields of study, the role of the sending state is by and large neglected when it comes to analyzing these processes. Yet, large sending states such as China increasingly aim to reach out to and control “their” diaspora, thus demonstrating their ability to utilize the global economic system and transnational migration regimes for their own means. By incorporating Chinese living beyond the borders of the People’s Republic (PRC), Beijing seeks to strengthen China’s international image and to foster economic modernization.